Identity, Religious Affiliation, and Politeness in an Introductory Arabic Language Textbook - Fatima El Zahraa; Heba Tawfiqe Abu Eyadah; Mukhshon Nawawi; Iman Matin; Haniah; Laily Maziyah (Arabic Education Department, Islamic Studies Faculty, Universitas Muhammadiyah Malang, 2025)
This study critically examined how an introductory Arabic language textbook for non-native learners represented linguistic variation, including Modern Standard Arabic, regional dialects, and cultural practices. Using qualitative content analysis within a critical discourse framework, the study analyzed Alif Baa (print and digital editions), covering ten instructional units, bilingual glossaries, and 28 video materials featuring fuṣḥā, Egyptian, Levantine, and mixed Arabic varieties. An evaluative checklist was employed to examine representations of non-standard Arabic, politeness strategies, social identities, intercultural communication, Islamic identity, learners’ linguistic ecology, pedagogy, and accessibility. The findings revealed that while the textbook promoted sociolinguistic awareness through selective inclusion of dialectal diversity, it simultaneously privileged dominant norms and limited sociopragmatic complexity. In conclusion, the study argues that Arabic language textbooks should move beyond tokenistic diversity by incorporating critical sociopragmatic explanations, non-native speaker models, and inclusive design principles to support equitable and critically informed language learning